Analisis Asosiasi Curah Hujan dengan Pola dan Prevalensi Kasus Demam Berdarah Dengue (DBD) di Provinsi Jawa Barat - Marsha Savira Agatha Putri; Nur Lathifah Syakbanah; Rizky Rahadian Wicaksono; Yunni Wahyuningsih (State Islamic University of Sunan Ampel, 2022)
One of the infectious diseases that have high morbidity and mortality rates is Dengue Hemorrhagic Fever (DHF) which is transmitted through the bite of Aedes aegypti and Aedes albopictus mosquitoes. In West Java Province, dengue cases fluctuated. So it is necessary to analyze and review the influence of weather on dengue cases in West Java Province with the pattern and prevalence of dengue cases in all cities and districts in West Java Province. This type of research is quantitative descriptive research by making exploratory observations and producing something general with a Geographic Information System approach. The location of this research is in all 27 districts and cities in West Java Province. Data on dengue cases in West Java Province is accessed from the West Java Provincial Health Office on the West Java Open Data platform (https://opendata.jabarprov.go.id/). Then the population data of West Java Province can be accessed at the Central Statistics Agency of West Java Province on the https://jabar.bps.go.id/ platform. Analysis of this research data for incidence is calculated by dividing the number of cases divided by the population and then multiplying by one hundred thousand, while the prevalence can be calculated by dividing the number of cases divided by the population and then multiplying by a thousand, and mapping using QGIS 3.16. From 2014 – 2020, the highest cases were in the city of Bandung and the highest prevalence was in the city of Sukabumi. there is a relationship between rainfall and DHF cases in West Java Province in 2014 - 2020 with a moderate correlation strength where rainfall plays a role in the incidence of DHF cases but is not absolute because it can still be influenced by other factors.